Perilaku pengelolaan sampah: pengaruh religiusitas, pengetahuan, jenis kelamin dan pekerjaan - Arifah, Lidyana; Ramahdani, Lili; Ulfah, Muthia; Mirawati, Mirawati (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2023)
Piles of rubbish in rivers, empty land, and burning rubbish still need to be solved in waste management in several areas in Tanah Datar, one of which is Nagari III Koto. Waste management is an essential environmental problem and requires active community participation. For this reason, knowing what factors encourage good waste management behavior is necessary. This research aims to find a correlation between religiosity, knowledge, intention, gender, and employment status with waste management behavior in Nagari III Koto Tanah Datar, West Sumatra. The amount of sample is 338 and the questionnaire about behavior, religiosity, knowledge, gender, and occupation using Likert scale and score. The results of the research show that the variables religiosity, intention, and gender do not significantly influence the behavior of the Nagari III Koto community in waste management. However, the knowledge and work variables significantly influence the behavior of the Nagari III Koto community in waste management by a sig value <0.05.